Harapa": The Metaphor of Woman’s Agony, Oppression and Helplessness - Shehzad, Muhammad Kamran; Jan, Ijaz Ahmad; Turab, Amir (sourcecoder, 2023)
Tahira Iqbal is a great contemporary novelist who has written marvellous novel like "Neeli Bar". "Harapa" is her third novel which has been published by Book Corner Jhelum in 2023. Apparently, it seems from the title of the novel that the history, culture and civilisation of five thousand years old society "Harapa" will be its subject, but a study of this novel reveals that it has diverse dimensions. This novel has been divided into three parts titled; "Abad Harapa", "Khandar Harapa", and "Fitrat Harapa", whose all parts are named after its characters. In this article woman’s helplessness, woman’s oppression on woman, envy, woman’s role and position in contemporary patriarchal society are made subject. This novel is a tragedy of woman’s agony, helplessness, obligation, and living in society with inferior status.